The Ugly American - William J. Lederer 1912-2009; Eugene Burdick (New York Fawcett Crest Book, 1961)
A fictional account of actual happenings in the East concerning American diplomatic policy--a fiery indictment of the kind of American abroad who misrepresents America Grest Giant d365
Keywords: Literature (3GdCOHs; General; Short stories, American; Americans -- Foreign countries -- Fiction; Internationality